Determinación del costo de producción en la empresa Caucho Industrias L. R. P. Cauchin de la ciudad de Cuenca, período: octubre – diciembre / 2013 - Enriquez Jaramillo, Jenny Adelaida (2014)
The development of this thesis entitled “DETERMINATION OF PRIME COST AT THE COMPANY RUBBER INDUSTRIES L.R.P. CAUCHIN, IN CUENCA CITY, PERIOD: OCTOBER – DECEMBER /2013” was carried out with the aim of contributing to an information base and useful technical procedures to improve prime cost determining on made goods. With its implementation, a better control on the three elements of cost “raw material, labor and indirect manufacturing costs” is achieved, allowing the manager to know the individual and total costs of production at the end of each batch, as benchmarks to the establishment of the product selling price, also keeping updated inventories of raw materials and finished goods. This work has been developed in compliance with the objectives therein, based on historical information and data collected over a period of three months on the company’s production process. With the implementation of costs system by production orders, the formats and basic records were designed and applied for better materials and labor control; a plan and an accounts specific manual have been developed in accordance with the company’s own activities; which allows the manager to have adequate information for decision-making on productive and economic development of the company. It is concluded that, with the development of this thesis, we could establish with certainty, individual and total costs on good manufactured in the period October – December 2013, at the company Rubber Industries L.R.P. Cauchin in Cuenca city. Therefore, it is recommended, in order to improve prime costs determining process, the costs system by proposed production orders is implemented, with its formats and records predesigned and applied in this work.